1996
DOI: 10.1093/carcin/17.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin-antioxidant micronutrients on the frequency of spontaneous and in vitro γ-ray-induced micronuclei in lymphocytes of donors: the age factor

Abstract: The effect of prolonged consumption of a vitamin-antioxidant mixture (VAM) on the frequency of spontaneous and in vitro gamma-radiation-induced micronuclei (MN) in peripheral blood lymphocytes in donors of various ages was investigated. Three groups of donors were recruited: (i) 56-83 years old (35 subjects), (ii) 23-30 years old (13 subjects), and (iii) 63-82 years old (12 subjects). Blood was sampled every 4 months for one year in all donors of the three groups. After the first sampling of blood, the donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…Micronucleus assay is a valuable complement to the chromosome aberration measurement and is comparatively easy to perform and inexpensive. Scientific studies have suggested that the presence of one or more micronuclei in peripheral erythrocytes in rodent is an accepted marker of chromosomal breakage or loss that occurred prior to the extrusion of the nucleus during erythrocyte differentiation (Venkatesh et al, 2007;Gaizev et al, 1996). , 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronucleus assay is a valuable complement to the chromosome aberration measurement and is comparatively easy to perform and inexpensive. Scientific studies have suggested that the presence of one or more micronuclei in peripheral erythrocytes in rodent is an accepted marker of chromosomal breakage or loss that occurred prior to the extrusion of the nucleus during erythrocyte differentiation (Venkatesh et al, 2007;Gaizev et al, 1996). , 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of neoplastic transformation is the accumulation of genetic lesions and is characterized by having aberrant chromosomes. The degree of chromosomal aberrations is correlated with tumor progression (Cheung and Loeb, 1997 (Gaizev et al, 1996). Cancer patients are often exposed to high level of DNA damaging agents.…”
Section: Introductionmentioning
confidence: 99%
“…Post-irradiation administration of vitamin C protected against wholebody irradiation-induced chromosome damage in mouse 38 . Dietary antioxidant supplementation with vitamins E, C, b-carotene, rutin, zinc and selenium reduced the frequency of radiation-induced micronuclei in human lymphocytes 39 . Combined administration of vitamins E, C and b-carotene before or after irradiation significantly reduced the radiation-induced micronuclei in mouse bone marrow 40 .…”
Section: Neutraceuticals and Phytochemicalsmentioning
confidence: 94%
“…Тест объектами для изучения цитогенетичес ких повреждений с помощью МЯ теста in vitro яв ляются клетки первичных и перевиваемых клеточ ных культур животных и человека: лимфоциты периферической крови [24], фибробласты кожи человека, фибробласты китайского хомячка, клет ки растений [25] и т. д. Для каждого объекта суще ствует своя специфика приготовления и окраски цитологических препаратов и подсчета МЯ.…”
Section: Wwwniiorramnruunclassified